Increasing the durability of the Ti-GFRP/CFRP contact with a layer of wear-resistant polymer composite coatings under vibration load conditions - Khimko, A.; Mikosyanchyk, O.; Khimko, M.; Klipachenko, V. (Problems of Tribology, 2026)
The development of aviation and the improvement of the flight characteristics of aircraft and helicopters requires the use of CFRP carbon fibers and GFRP fiberglass in power structures. The vibration load factor is an integral part of the aircraft design. With vibrations, a contact that we thought was nominally stationary begins to move at the micro level over time. Movement between parts is sufficient for the catastrophic development of fretting-corrosion wear of contacting parts, followed by the development of fatigue cracks and structural failure. Therefore, it is very important to pay attention to increasing the durability of contact made of Ti-GFRP/CFRP materials under vibration loads, since as a rule, these are power parts of aircraft, damage to which significantly reduces the reliability of the structure and increases the risk of fatigue cracks, especially in parts made of titanium alloys. One method of increasing the durability of the Ti-GFRP/CFRP contact is the use of intermediate "sacrificial" materials that are triggered during operation and replaced during repairs, but protect the contact from damage. The paper analyzes wear-resistant composite materials and determines what materials F4К15М5 and ZX550 are most suitable for this. It was found that during tests in the Ti-F4К15М5-GFRP system, the metal surface is completely protected by spreading an intermediate material on the surface. The mechanisms of wear of intermediate materials and their effect on contact under vibration loads have been determined.